The management of chronic traumatic ulcer in oral cavity - Maharani Laillyza Apriasari (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2012)
Background: The traumatic ulcer is one of the most common oral mucosal lesions. The etiology of traumatic ulcer may result from mechanical trauma, as well as chemical, electrical, or thermal stimulus, may also be involved in addition, fractured, malposed, or malformed teeth. The clinical manifestation of traumatic ulcer are ulcer, have a yellowish floor, fibrinous center, red and inflammatory margin without induration. Purpose: The purpose of this case report is to present how to manage the patient with the chronic traumatic ulcer in oral cavity. Case: This case report is about the patient with chronic ulcer in oral cavity. Intra oral examination showed on the right tongue margin appeared the major ulcer, single, diameter 1,5 cm, pain, white color, induration and irreguler margin around the ulcer. The patient had been suffering it for 5 months. She had come to a lot of dentist and the oral maxillofacial surgery, but they could not heal the ulcer. The dental occlusion of the patient, especially 17 and 47 then 15 and 45 teeth was looked bitten the right tongue. It underlied to get the clinical diagnosis as the chronic traumatic ulcer. Case management: The main therapy of traumatic ulcer is eliminiting the etiology factor, so that decided to do teeth extraction 45 and 47 that was looked linguversion position on 45 degrees. Before doing the teeth extraction, the patient was referred to take complete blood count (CBC), blood glucose examination and biopsy. The monitoring of the ulcer must be done until 2 weeks after the teeth extraction. If the lesion was persistent, it is suspected as malignancy. Conclusion: It can be concluded that the main management of chronic traumatic ulcer in oral cavity is removing the etiology factors. If the ulcer is still persistent after 2 weeks from the etiology factor had been removing, it is suspected as the malignancy that is needed biopsy examination to get the final diagnosis.Latar belakang: Ulkus traumatikus adalah salah satu lesi pada mukosa mulut yang sering terjadi. Penyebab ulkus traumatikus adalah adanya trauma mekanik, seperti kimia, elektrik atau suhu, selain itu dapat pula terjadi karena fraktur, malposisi atau malformasi gigi. Manifestasi klinis dari ukus traumatikus adalah ulser, dasar berwarna kuning, pada bagian tengah tampak fibrin, pinggiran berwarna merah dan mengalami keradangan tanpa adanya indurasi. Tujuan: Tujuan dari laporan kasus ini adalah untuk melaporkan bagaimana penatalaksanaan pasien dengan ulkus traumatikus kronis pada rongga mulut. Kasus: Kasus ini melaporkan tentang ulser kronis yang terjadi pada rongga mulut. Pemeriksaan pada rongga mulut menunjukkan pada pinggir lidah kanan tampak ulser mayor, tunggal, diameter 1,5 cm, sakit, berwarna putih, pinggiran sekitarnya tampak indurasi dan tidak teratur. Ulser terjadi selama 5 bulan. Pasien mengunjungi banyak dokter gigi dan spesialis bedah mulut, tetapi ulser tidak dapat disembuhkan. Pada saat pasien oklusi, pada gigi, 17 dengan 47 serta gigi 15 dengan 45 tampak lidah sebelah kanan tergigit. Hal ini yang mendasari diagnosis sementaranya adalah ulkus traumatikus kronis. Tatalaksana kasus: Penanganan utama dari ulkus traumatikus adalah menghilangkan faktor penyebab, oleh sebab itu dilakukan ekstraksi pada gigi 45 dan 47 yang terlihat posisi linguoversi 45 derajat. Sebelum gigi-gigi tersebut diekstraksi, pasien dirujuk untuk melakukan pemeriksaan darah lengkap, gula darah dan biopsi. Ulser harus tetap dimonitor sampai 2 minggu pasca ekstraksi. Jika lesi menetap, maka ini diduga Squamous Cell Crsinoma. Kesimpulan: Dapat disimpulkan bahwa penatalaksanaan utama dari ulkus traumatikus kronis pada rongga mulut adalah dengan menghilangkan faktor penyebab. Ulser yang persisten setelah 2 minggu setelah faktor penyebab dihilangkan, maka diduga suatu keganasan yang perlu pemeriksaan biopsi untuk menegakkan diagnosis akhir.